Inovasi Diagnosis Meningitis Streptococcus Suis: Tantangan dan Solusi - Komang Trisna Sumadewi; Saktivi Harkitasari; Dewa Ayu Agung Alit Suka Astini; Luh Gede Evayanti (Fakultas Kedokteran Universitas Trisakti, 2026)
Streptococcus suis (S. suis) is an important zoonotic pathogen that causes severe infections in humans, including meningitis, sepsis, and endocarditis. S. suis meningitis remains a public health concern, particularly in regions with high pork consumption, pig farming, or occupational exposure to pigs and pork products. This narrative review synthesizes current evidence on pathogenesis, diagnostic gaps, and emerging point-of-care strategies. The disease develops through sequential colonization, bloodstream invasion, disruption of the blood-brain barrier, entry into the central nervous system, and meningeal inflammation. Virulence factors, including capsular polysaccharide, suilysin, collagenase-like protease, and zinc metalloproteinase C, contribute to immune evasion, endothelial injury, and increased barrier permeability. Conventional cerebrospinal fluid culture enables bacterial isolation and antimicrobial susceptibility testing, but its diagnostic yield may decrease after prior antibiotic exposure, and its turnaround time is slow. PCR-based methods offer faster targeted detection, with reported diagnostic performance of approximately 92–100% and potential results within less than 4 hours in optimized workflows. Metagenomic next-generation sequencing improves detection in culture-negative or complex cases but remains limited by cost, infrastructure, and interpretation challenges. LAMP, RPA-lateral flow assays, biosensors, and CRISPR-based platforms are promising but require clinical validation using human cerebrospinal fluid. Future research should prioritize accuracy, affordability, accessibility, and implementation in endemic settings globally.